Ferramenta de gestão de riscos aplicada à terceirização de mão de obra na administração pública - Veloso, Marinalva Domingues Mendes (2017)
Due to successive legislation, Brazil is in the process of increasing the flexibility of the use of outsourced labor, such as the recent approval of Law 13,429 of 2017, which regulates the outsourcing of labor in public and private organizations and the Normative Instruction nº 05/2017 Specific MP for the outsourcing of services in the Federal Public Administration. Thus, when analyzing the historical context of the outsourcing of labor and its growth in the Federal Universities from the federal programs of restructuring and university expansion, beginning in 2007, this study sought to contribute to the knowledge about the use of labor outsourced in the public sector, as well as the risks involved in this practice, specifically in UNIFAL-MG. So the question arises: What are the risks involved in the use of outsourcing of labor for UNIFAL-MG? In response to the question, the present study aimed to identify and analyze the risks involved in the outsourcing of labor in UNIFAL-MG from the restructuring and university expansion, based on the methodological roadmap for descriptive exploratory research using resources bibliographical and documentary, with qualitative evaluation of the results. After examining the expansion and university restructuring in UNIFAL-MG, it was verified that there was an increase in the outsourced workforce due to the university's growth. Subsequently, fourteen risks of outsourcing labor to which UNIFAL-MG is exposed were identified through institutional records. Additionally, a tool for risk mapping was elaborated based on the main methodologies for risk management in Public Administration.